Feasibility of using an epigenetic marker of risk for lung cancer, methylation of p16, to promote smoking cessation among US veterans. Issue 1 (30th June 2014) - Shofer, Scott; Beyea, Matthew; Li, Sufeng; Bastian, Lori A; Wahidi, Momen M; Kelley, Michael; Lipkus, Isaac M
Abstract : Introduction: Providing smokers feedback using epigenetic markers of lung cancer risk has yet to be tested as a strategy to motivate smoking cessation. Epigenetic modification of Rb-p16 ( p16 ) due to tobacco exposure is associated with increased risk of developing lung cancer. This study examined the acceptance of testing for methylated p16 and the understanding of test results in smokers at risk for development of lung cancer. Methods: Thirty-five current smokers with airways obstruction viewed an educational presentation regarding p16 function followed by testing for the presence of methylated p16 in sputum. Participants were offered smoking cessation assistance and asked to complete surveys at the time of enrolment regarding their understanding of the educational material, perception of risk associated with smoking and desire to quit. Participants were notified of their test result and follow-up surveys were administered 2 and 10 weeks after notification of their test result. Results: Twenty per cent of participants had methylated p16 . Participants showed high degree of understanding of educational materials regarding the function and risk associated with p16 methylation. Sixty-seven per cent and 57% of participants with low-risk and high-risk test results, respectively, reported that the information was more likely to motivate them to quit smoking. Smoking cessation rates were similar between methylated and non-methylated participants. Conclusions: Testing for an epigenetic marker of lung cancer risk is accepted and understood by active smokers. A low-risk test result does not decrease motivation to stop smoking. Trial registration number: NCT01038492.